IMPLEMENTASI KURIKULUM MERDEKA BERBASIS P5: STRATEGI MANAJEMEN KURIKULUM DALAM MENINGKATKAN KOMPETENSI DAN KARAKTER PROFIL PELAJAR PANCASILA DI SMA NEGERI 1 KANDAT - Ridwanulloh, M. Ubaidillah; Rahayu, Sylla Indah Ning; Mulyaningsih, Galih Wikan Ratih (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2025)
This study discusses the implementation of the Pancasila Student Profile Strengthening Project (P5) through curriculum management at SMA Negeri 1 Kandat to improve students' competency and Pancasila character formation. P5 is part of the Independent Curriculum which aims to link educational theory with real-world situations. Through a qualitative approach with a case study type, this study explores the strategies for planning, organizing, implementing, and evaluating the implementation of the Independent Learning curriculum. Data was collected through interviews, observations, and documentation. The results showed that P5-based character formation succeeded in creating space for students to develop character and improve skills in accordance with Pancasila values. The P5 project encouraged collaboration between teachers and increased student involvement in the learning process. In conclusion, this curriculum management strategy contributed to the development of independent curriculum management in project-based high schools and succeeded in instilling the character of Pancasila student profiles.